2012
DOI: 10.1371/journal.pone.0038024
|View full text |Cite
|
Sign up to set email alerts
|

RNA Folding and Catalysis Mediated by Iron (II)

Abstract: Mg2+ shares a distinctive relationship with RNA, playing important and specific roles in the folding and function of essentially all large RNAs. Here we use theory and experiment to evaluate Fe2+ in the absence of free oxygen as a replacement for Mg2+ in RNA folding and catalysis. We describe both quantum mechanical calculations and experiments that suggest that the roles of Mg2+ in RNA folding and function can indeed be served by Fe2+. The results of quantum mechanical calculations show that the geometry of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 66 publications
6
74
0
Order By: Relevance
“…Once contained in these interlayers, the orthophosphates are condensed to various pyrophosphate species such as trimetaphosphate [167,169], with the proximal ferrous iron atoms acting in the same role as the five magnesium ions that neutralize phosphate-phosphate repulsion, packed closely around the phosphates in the H þ -pyrophosphatase described by Lin et al [118]. Such diadochic substitution has been demonstrated by Athavale et al [177] whereby ferrous iron substitutes for magnesium in clamping phosphates in RNA conformations in the Group I intron P4 -P6 domain of Tetrahymena thermophila. The interlayer water molecules in the oxidized end-member of fougerite should permit proton hopping from water molecule to water molecule via a Grotthuss-type mechanism much as they do in the exit/entry channel to the extant enzyme [119,178,179].…”
Section: A Pyrophosphatase Engine: Chemiosmosis For Freementioning
confidence: 89%
“…Once contained in these interlayers, the orthophosphates are condensed to various pyrophosphate species such as trimetaphosphate [167,169], with the proximal ferrous iron atoms acting in the same role as the five magnesium ions that neutralize phosphate-phosphate repulsion, packed closely around the phosphates in the H þ -pyrophosphatase described by Lin et al [118]. Such diadochic substitution has been demonstrated by Athavale et al [177] whereby ferrous iron substitutes for magnesium in clamping phosphates in RNA conformations in the Group I intron P4 -P6 domain of Tetrahymena thermophila. The interlayer water molecules in the oxidized end-member of fougerite should permit proton hopping from water molecule to water molecule via a Grotthuss-type mechanism much as they do in the exit/entry channel to the extant enzyme [119,178,179].…”
Section: A Pyrophosphatase Engine: Chemiosmosis For Freementioning
confidence: 89%
“…These Mg 2+ ions are exposed to the solvent side of the large subunit allowing their potential replacement with Fe 2+ . In support of iron binding by rRNA, previous studies have shown that Fe 2+ , being a divalent cation with similar ionic radii and geometric properties as Mg 2+ , is capable of structural and functional replacement of Mg 2+ in nucleic acids (33,37,(52)(53)(54)(55). It is clear, however, that not every Mg 2+ ion bound to the ribosome could be substituted by iron with the same efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Perturbations to the landscape, such as environmental change, might also uncover evolutionary pathways. Indeed, the RNA landscape itself is likely to be highly dependent on conditions such as ionic composition (e.g., the concentration of Mg 2+ and other divalent cations), presence of cofactors, temperature, and water activity, and therefore may be quite dynamic in response to changing conditions (53,54). Fitness peaks for one functional activity can be near in sequence space to peaks for another activity, potentially leading to adoption of new function (55)(56)(57)(58), suggesting that changing selection conditions could have an important role.…”
Section: Discussionmentioning
confidence: 99%